2009
DOI: 10.1007/s10459-009-9208-9
|View full text |Cite
|
Sign up to set email alerts
|

Developing clinical competency in crisis event management: an integrated simulation problem-based learning activity

Abstract: This study aimed to evaluate the integration of a simulation based learning activity on nursing students' clinical crisis management performance in a problem-based learning (PBL) curriculum. It was hypothesized that the clinical performance of first year nursing students who participated in a simulated learning activity during the PBL session would be superior to those who completed the conventional problem-based session. The students were allocated into either simulation with problem-based discussion (SPBD) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 18 publications
3
43
0
Order By: Relevance
“…Simulation [21], PBL [19] or SIM-PBL [11] have been alternative ways to improve stu-dents' ability to perform the physical examination appropriately in varied clinical situations. Furthermore, previous studies have shown that SIM-PBL is better than PBL alone in teaching those skills to nursing students [11] and medical students [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulation [21], PBL [19] or SIM-PBL [11] have been alternative ways to improve stu-dents' ability to perform the physical examination appropriately in varied clinical situations. Furthermore, previous studies have shown that SIM-PBL is better than PBL alone in teaching those skills to nursing students [11] and medical students [12].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that simulation, coupled with PBL, can offer nursing students a more integrated learning process and a wider spectrum of clinical education. Simulation integrated with problem-based learning (SIM-PBL) has been used to improve clinical competency [11], critical assessment [12], academic achievement [13], problem solving [9], and self-efficacy (SE) [14] for nursing and medical students.…”
Section: Introductionmentioning
confidence: 99%
“…Universities currently face larger class sizes, distance learning, and the expectation to do more with less (Tompson, 2003;Sibbald, 2003;Alexiou, 2004;Brands, 2009). In health care education, students must not only gain knowledge, but also master clinical and personal skills (Kinkade, 1995;Schlicht, 1997;Fuhrman, 2001;Sibbald, 2003Sibbald, , 2004Kiegaldie, 2006;Kluge, 2007;Orr, 2007;Tsai, 2008;Bambini, 2009;Brands, 2009;Paige, 2009;Kameg, 2010;Liaw, 2010). Simulations have commonly been useful as supplements in teaching complex concepts in pharmacology and pharmacokinetics (Li, 1995;Sewell, 1996;Haworth, 1997;Hedaya, 1998;Boje, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Simulations have commonly been useful as supplements in teaching complex concepts in pharmacology and pharmacokinetics (Li, 1995;Sewell, 1996;Haworth, 1997;Hedaya, 1998;Boje, 2005). Mannequin simulations have been used to develop communication, assessment, and clinical skills (Bambini, 2009;Brands, 2009;Kameg, 2010;Liaw, 2010). Sibbald and Schlicht developed virtual patient case studies (Schlicht, 1997;Sibbald, 2003;2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation